PENGARUH POLA PIKIR KEWIRAUSAHAAN DAN ADVERSITY QUOTIENT TERHADAP MINAT BERWIRAUSAHA (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Tangerang) - Nining Purwaningsih; Teknik Megaster (Universitas Muhammadiyah Tangerang, 2019)
The purpose of this study was to analyze how much influence the entrepreneurial mindset and adversity quotient had on the interest in entrepreneurship in students of the Faculty of Economics and Business, University of Muhammadiyah Tangerang. The research sample was 98 people. Convenience sampling was used for sampling techniques. Data collection was done by distributing questionnaires. The method used in this study is the verification method to determine the effect of the entrepreneurial mindset and adversity quotient on the interest in entrepreneurship in students of the Faculty of Economics and Business, University of Muhammadiyah Tangerang. The test statistics used are designing structural models, designing measurement models, building path diagrams, testing the appropriate models. Suitability test of structural models and hypotheses using SmartPLS 3.0 software. The results showed that the mindset of entrepreneurship and adversity quotient had a significant influence on the interest in entrepreneurship.Keywords: entrepreneurial mindset, adversity quotient, interest in entrepreneurship